Effect of Loss Aversion on Company Performance in Indonesia - Grace Turangan; Sung Suk Kim (FEB Universitas Sam Ratulangi Manado, 2022)
The loss aversion bias tends to be done by investors to avoid losses that will psychologically be felt greater than the gain they receive. The exploration on this research in Indonesia, is to see how the impact of investor loss aversion to company economic performance. Using quarterly observation data of 7,535 on 190 companies that are still active, exclude the financial sector and registered as members of KOMPAS-100 during the period 2009-2019. In this research, a regression model with panel data, developed to test the hypothesis which formed on this research, by using two dependent variables ROA and Tobin's Q to see if both variable are supporting the previous research. The results of empirical research prove that both models formed proved that loss aversion impacted negative affect on both selected dependent variables, whether it is with additional control variable or not.